Analytical study of tensegrity lattices for mass-efficient mechanical energy absorption. Issue 1 (March 2019) - Goyal, Raman; Peraza Hernandez, Edwin A; Skelton, Robert E
This article studies tensegrity structures known as "D-bar" systems for applications as lightweight components for mechanical energy absorption. Aerospace structures such as planetary landers, designed to absorb energy from large impact loads while requiring minimal mass, would benefit from such components. Previous studies showed that D-bar systems support compressive loads with minimal mass compared with continuum options such as single columns. In this work, analytical equations for the mechanical (elastic) energy stored in D-bar systems of any complexity (a quantity proportional to the number of strings/bars in the system) are derived for the first time. The energy stored in D-bar systems is compared with that of bent buckled beams used in "flexible-bar tensegrity" concepts, which were proposed in the literature as energy absorption components for planetary landers. Comparisons are made between D-bar systems and bent buckled beams as isolated components subjected to a compressive load and as components of planetary landers. In all comparisons, the results show that D-bar systems of low complexity allow for higher energy storage and lower mass than bent buckled beams. Thus, it is concluded that D-bar systems can enhance the design of planetary landers and other applications that need lightweight mechanical energy absorption components.